At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
(x - 2)² + 1 = 0
(x - 2)(x - 2) + 1 = 0
x(x - 2) - 2(x - 2) + 1 = 0
x(x) - x(2) - 2(x) + 2(2) + 1 = 0
x² - 2x - 2x + 4 + 1 = 0
x² - 4x + 4 + 1 = 0
x² - 4x + 5 = 0
x = -(-4) ± √((-4)² - 4(1)(5))
2(1)
x = 4 ± √(16 - 20)
2
x = 4 ± √(-4)
2
x = 4 ± 2i
2
x = 2 ± i
x = 2 + i U x = 2 - i
The solution set is {2 ± i}.
(x - 2)(x - 2) + 1 = 0
x(x - 2) - 2(x - 2) + 1 = 0
x(x) - x(2) - 2(x) + 2(2) + 1 = 0
x² - 2x - 2x + 4 + 1 = 0
x² - 4x + 4 + 1 = 0
x² - 4x + 5 = 0
x = -(-4) ± √((-4)² - 4(1)(5))
2(1)
x = 4 ± √(16 - 20)
2
x = 4 ± √(-4)
2
x = 4 ± 2i
2
x = 2 ± i
x = 2 + i U x = 2 - i
The solution set is {2 ± i}.
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.